The Dissolution of Dawkins’ Riddle Is Not So Hard - Bucci, Andrea (Journal of NeuroPhilosophy, 2023)
In this paper, I propose a metaphysics of group selection that solves the conundrum without appealing to the biological research in modern evolutionism but taking it in the background and citing it when needed. In my opinion, the group selection is practically possible and it does not contrast with the other fact, that natural selection involves individuals’ genes only. I propose this metaphysics as a reasoned narration of how the group selection works and I will show how the conundrum can be solved. The point seems to me that differently from what done till now, the description of the evolutionary mechanisms of individuals at the genes level must to correspond to the behaviour of individuals us such at least for what we know about it.